Developing a mathematical substantiation for the physical modelling of the soilripping equipment work process - Pelevin, Leonid; Gorbatyuk, Ievgenii; Zaichenko, Stefan; Shalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2017)
In the course of a theoretical study, we examined ways to enhance effectiveness of the ripping unit by improving its control system. This is important because the most effective technique for destroying frozen and rocky soils in terms of machine performance and the cost of soil development is the horizontal layer-wise loosening by mounted rippers based on powerful tractors. During work of the ripping unit, it running equipment interacts with soil, which causes uncontrolled displacements of the working body in space. This leads to a change in the depth of loosening and, consequently, to a change in the soil reaction on the working body. The soil reactions during its destruction that were identified and described lead to uncontrolled displacement of the working body with low-frequency and high-frequency oscillations that act on the mounted equipment, reducing the reliability of the working equipment. The mathematical apparatus that we constructed made it possible to formulate conditions for the minimization of dynamic loads on the base machine by the creation of a controlling signal to the mounted equipment of a ripping unit. Depending on the statistical analysis of terrain relief, by levelling a section, it is possible to send a controlling signal to the mounted equipment of the working body, which would reduce dynamic loads. Adequacy of the proposed models of micro relief and work process of the ripping unit is achieved based on the statistical processing of soil relief, the introduction of a controlling signal for the motion of a base machine and the operational equipment